Legal Certainty on Dishonorable Notary Dismissal for Serious Violations - Gama Dwipa Dinar Nur Rensa; Rachmi Sulistyarini; Amelia Sri Kusuma Dewi (Faculty of Law, Merdeka University Surabaya, Indonesia, 2027)
This study aims to analyze the legal regulation governing the dishonorable dismissal of notaries due to serious violations of their statutory duties and prohibitions and to formulate a normative reformulation of the relevant legal provisions. This research employs a normative legal research method using statutory, conceptual, and case approaches through the analysis of legislation, legal doctrines, and relevant judicial decisions. Unlike the study by Iman Zenza Bronica, which focuses on the benchmarks for administrative sanctions, the research of Nur Afni Hidayanti, which examines the legal consequences of violations on the validity of notarial deeds, and the study by Nilna Muna Yuliandari, which analyzes legal remedies against the dismissal of notaries, this research specifically addresses the ambiguity of Article 12(d) of Law Number 2 of 2014, particularly the phrase